Cost Effectiveness of Mobile Health for Antenatal Care and Facility Births in Nigeria. Issue 4 (5th November 2018) - Bowser, Diana M.; Shepard, Donald S.; Nandakumar, Allyala; Okunogbe, Adeyemi; Morrill, Tyler; Halasa-Rappel, Yara; Jordan, Monica; Mushi, Farida; Boyce, Carolyn; Oluwayemisi, Erhunmwunse
Background: The use of mobile technology in the health sector, often referred to as mHealth, is an innovation that is being used in countries to improve health outcomes and increase and improve both the demand and supply of health care services. This study assesses the actual cost-effectiveness of initiating and implementing the use of the mHealth as a supply side job aid for antenatal care. The study also estimates the cost-effectiveness ratio if mHealth was also used to encourage and track women through facility delivery. Methods: The methodology utilized a retrospective, micro-costing technique to extract costing data from health facilities and administrative offices to estimate the costs of implementing the mHealth antenatal care program and estimate the cost of facility delivery for those that used the antenatal care services in the year 2014. Five different costing tools were developed to assist in the costing analysis. Findings: The results show that the provision of tetanus toxoid vaccination and malaria prophylaxis during pregnancy and improved labor and delivery during facility delivery contributed the most to mortality reductions for women, neonates and stillbirths in mHealth facilities versus non-mHealth facilities. The cost-effectiveness ratio of this program for antenatal care and no demand-side generation for facility delivery is US13, 739 per life saved. The cost-effectiveness ratio adding in an additional demand-side generation for facility births reduces to US9, 806 per life saved. Conclusion: These results show that mHealth programs are inexpensive and save a number of lives for the dollar investment and could save additional lives and funds if women were also encouraged to seek facility delivery.